ELECTROCOAGULATION/ELECTROFLOCULATION FOR WASTEWATER TREATMENT: NON-CONVENTIONAL ELECTRODES AND COUPLING OF TECHNIQUES. - Aratijo Grecco, Luis Henrique [UNESP]; Araujo Souza, Barbara Camila de [UNESP]; Boldrin Zanoni, Maria Valnice [UNESP] (Soc Brasileira Quimica, 2021)
Electrocoagulation-electroflotation (EC) technology is a well-known wastewater treatment process that consists of applying electric current to remove contaminants without requiring the addition of chemicals that can generate secondary pollutants. Once they are the most widely used, iron and aluminum electrodes are considered conventional, however they leave unwanted residues, which will give a yellowish-brown color to the treated water, in the case of iron electrodes, and are associated with potential risks to human health, in the case of aluminum electrodes. In this regard, the study of non-conventional electrodes capable of circumventing those problems is essential for the development of more effective wastewater treatments. In this review article, a brief presentation will be made of the history of electrofloculation followed by a brief discussion of conventional electrodes and the mechanisms that govern the processes of removing contaminants by the electrocoagulation process. Subsequently, the non-conventional electrodes reported in the literature up to the present moment will be presented, as well as their potential, applications and performance when applied in water treatment. Finally, will be discussed the coupling of the electroflotation with other water treatment techniques towards achieving a better-quality reuse water.
Keywords: nickel electrodes; advanced oxidative process; titanium electrodes; zinc electrodes; steel electrodes; electrochemistry